Planet of the apes - Burton, Tim; Twentieth Century Fox (California : 20th Century Fox Home Entertainment, 2001)
In a remake of the original film, after an astronaut crash-lands on an uncharted planet he finds himself at odds with a society in which apes are the rulers - and humans are little more than slaves
[Disc 1]: Main feature -- Enhanced viewing mode -- Commentaries -- Cast profiles -- Crew profiles -- DVD-ROM features -- Nuon features -- [Disc 2]: Making of the apes -- Screen tests -- Multi-angle featurettes -- Limbo's quadrangle -- Sandar's house -- Extended scenes -- Concept art gallery, scenes and props -- DVD-ROM to access extra features and experience the film in a unique way -- Promotional works -- Trailers and TV spots
Title from title screen
Cast: Mark Wahlberg, Tim Roth, Helena Bonham Carter, Michael Clarke Duncan, Kris Kristofferson, Estella Warren, Paul Giamatti
DVD Format
With optional Cantonese, English, Korean, Mandarin or Thai subtitles
Keywords: Primates -- Evolution -- Drama; Survival after airplane accidents, shipwrecks, etc. -- Drama; Time travel -- Drama